(untitled) - Herausgebergremium: Ruth Bielfeldt, Peter Eich, Stefan Feuser, Christoph Horn, Joseph Maran, Gernot Michael Müller, Oliver Schelske, Katharina Volk, Johannes Wienand und Paul Zanker; Schriftleitung: Gernot Michael Müller (verantwortlich), Adrian Weiß (Gnomon, 2004)
As a critical journal for all classical studies, the GNOMON fosters the links between the distinct classical disciplines. It has thus an exceptional position among the classical review journals and allows familiarization with research and publications in neighbouring disciplines. The reviews address an international readership from all fields in classical studies. The GNOMON publishes reviews in German, English, French, Italian and Latin.The GNOMON is published in eight issues a year.